Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine the value of [tex]\(a\)[/tex] for which the polynomial [tex]\(4x^4 + 2x^3 - 3x^2 - ax - 28\)[/tex] has [tex]\(-2\)[/tex] as a zero, we need to substitute [tex]\(-2\)[/tex] for [tex]\(x\)[/tex] in the polynomial and set the equation equal to zero.
Let's substitute [tex]\(x = -2\)[/tex]:
[tex]\[4(-2)^4 + 2(-2)^3 - 3(-2)^2 - a(-2) - 28 = 0\][/tex]
Step-by-step calculation:
1. Calculate [tex]\(4(-2)^4\)[/tex]:
[tex]\[ 4 \times (-2)^4 = 4 \times 16 = 64 \][/tex]
2. Calculate [tex]\(2(-2)^3\)[/tex]:
[tex]\[ 2 \times (-2)^3 = 2 \times (-8) = -16 \][/tex]
3. Calculate [tex]\(-3(-2)^2\)[/tex]:
[tex]\[ -3 \times (-2)^2 = -3 \times 4 = -12 \][/tex]
4. The constant term is:
[tex]\[ -28 \][/tex]
5. Combine the calculated terms:
[tex]\[ 64 - 16 - 12 - (-2a) - 28 \][/tex]
Combine and simplify the expression:
[tex]\[ 64 - 16 - 12 - 28 + 2a = 0 \][/tex]
6. Sum the constants:
[tex]\[ 64 - 16 - 12 - 28 = 8 \][/tex]
7. Incorporate the remaining terms to solve for [tex]\(a\)[/tex]:
[tex]\[ 8 + 2a = 0 \][/tex]
8. Isolate [tex]\(a\)[/tex] by subtracting 8 from both sides:
[tex]\[ 2a = -8 \][/tex]
9. Finally, solve for [tex]\(a\)[/tex] by dividing both sides by 2:
[tex]\[ a = -4 \][/tex]
Thus, the value of [tex]\(a\)[/tex] is [tex]\(-4\)[/tex].
So the correct answer is:
c) [tex]\(-4\)[/tex]
Let's substitute [tex]\(x = -2\)[/tex]:
[tex]\[4(-2)^4 + 2(-2)^3 - 3(-2)^2 - a(-2) - 28 = 0\][/tex]
Step-by-step calculation:
1. Calculate [tex]\(4(-2)^4\)[/tex]:
[tex]\[ 4 \times (-2)^4 = 4 \times 16 = 64 \][/tex]
2. Calculate [tex]\(2(-2)^3\)[/tex]:
[tex]\[ 2 \times (-2)^3 = 2 \times (-8) = -16 \][/tex]
3. Calculate [tex]\(-3(-2)^2\)[/tex]:
[tex]\[ -3 \times (-2)^2 = -3 \times 4 = -12 \][/tex]
4. The constant term is:
[tex]\[ -28 \][/tex]
5. Combine the calculated terms:
[tex]\[ 64 - 16 - 12 - (-2a) - 28 \][/tex]
Combine and simplify the expression:
[tex]\[ 64 - 16 - 12 - 28 + 2a = 0 \][/tex]
6. Sum the constants:
[tex]\[ 64 - 16 - 12 - 28 = 8 \][/tex]
7. Incorporate the remaining terms to solve for [tex]\(a\)[/tex]:
[tex]\[ 8 + 2a = 0 \][/tex]
8. Isolate [tex]\(a\)[/tex] by subtracting 8 from both sides:
[tex]\[ 2a = -8 \][/tex]
9. Finally, solve for [tex]\(a\)[/tex] by dividing both sides by 2:
[tex]\[ a = -4 \][/tex]
Thus, the value of [tex]\(a\)[/tex] is [tex]\(-4\)[/tex].
So the correct answer is:
c) [tex]\(-4\)[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.